DEVELOPMENT OF READING TEACHING MATERIALS BASED ON RIAU MALAY FOLKLORE TEKTS TO ENHANCE STUDENTS’ LITERACY QUALITY - Arifannisya, Fira Salsa; Asnawi, Asnawi (JMIE (Journal of Madrasah Ibtidaiyah Education), 2024)
The reading teaching materials used by students of the Indonesian Language and Literature Education study program at Riau Islamic University do not yet contain folklore texts. Based on field data, there are still not many reading teaching materials found in the Pekanbaru Riau area. The aim of this research is to describe the need for reading teaching materials containing Riau Malay folklore texts to improve the quality of student literacy. This research is qualitative research that uses questionnaires and interviews as research instruments. The respondents in this research were students of the Indonesian Language and Literature Education study program at Riau Islamic University who had taken the aesthetic reading course. The results of this research are in the form of a description of the need for reading teaching materials containing Riau Malay folklore texts to improve the quality of literacy for students in accordance with the appropriateness standards for teaching materials which include (1) aspects of appropriateness of teaching materials, (2) aspects of appropriateness of content, (3) aspects presentation of teaching materials, (5) linguistic aspects supporting teaching materials for reading folklore.